Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fnins.2020.586108
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin-Deficient Neurons and Astrocytes Display Normal Mitochondrial Phenotypes

Abstract: Presenilin 1 (PS1) and Presenilin 2 (PS2) are predominantly known as the catalytic subunits of the γ-secretase complex that generates the amyloid-β (Aβ) peptide, the major constituent of the senile plaques found in the brain of Alzheimer's disease (AD) patients. Apart from their role in γ-secretase activity, a growing number of cellular functions have been recently attributed to PSs. Notably, PSs were found to be enriched in mitochondria-associated membranes (MAMs) where mitochondria and endoplasmic reticulum … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…Primary cultures of neurons were obtained from postnatal day 0 pups as previously described [ 24 , 90 ], with some modifications. Briefly, brain tissues (containing cortices and hippocampi) were isolated by dissection in ice-cold HBSS/0.2% glucose and meninges were removed.…”
Section: Methodsmentioning
confidence: 99%
“…Primary cultures of neurons were obtained from postnatal day 0 pups as previously described [ 24 , 90 ], with some modifications. Briefly, brain tissues (containing cortices and hippocampi) were isolated by dissection in ice-cold HBSS/0.2% glucose and meninges were removed.…”
Section: Methodsmentioning
confidence: 99%
“…Now, ample evidence showed that PS2 is linked to Alzheimer's disease [18], and mutations in PS2 are considered to be reliable genetic markers of Alzheimer's disease [19]. Recent studies have also indicated that PS2 disrupts mitochondrial homeostasis by altering mitochondrial calcium input [20], mitochondria-ER coupling [21], mitochondrial phenotypes [22], the mitochondrial oxidative capacity [23], mitochondrial oxygen consumption, the mitochondrial membrane potential [24] and mitochondria-induced cell death [25]. More importantly, mutations in PS2 have been linked with the development of dilated cardiomyopathy and heart failure [26].…”
Section: Ivyspringmentioning
confidence: 99%
“…These impairments were reversed upon PSEN2 re-expression, underscoring a specific implication for PSEN2 in the maintenance of mitochondrial morphology and homeostasis. However, and surprisingly, none of these disruptions could be recapitulated in primary neuronal nor astrocytic cells isolated from PSEN2-deficient transgenic mice (Contino et al, 2021 ). Moreover, the idea that upregulated MAMs could participate in AD pathogenesis was recently challenged.…”
Section: Mams In Pd and Admentioning
confidence: 99%